Evaluación del estado actual de eutrofización de la laguna de Yahuarcocha - Méndez Landázuri, Oscar Danilo (2022)
The Yahuarcocha lagoon intuits an ecosystem of great ecological, economic and tourist category in Ecuador.This research work starts from the identification of the problem and the central objective of 'To evaluate the current state of eutrophication and its impact on the waters of the Yahuarcocha lagoon' to determine the areas most affected by eutrophication, due to nutrient contamination or the presence of chlorophyll pigments in freshwater bodies. For the investigation, the systematic diagonal sampling method was used to cover a greater coverage of the lagoon\; With the use of devices, samples were taken in different strata and parameters such as: turbidity, phosphates, nitrates, ammonium, dissolved oxygen, color, chlorophyll, among others, were analyzed. The conclusions showed that the current state of the waters of the Yahuarcocha lagoon are in a Eutrophic state, according to the results obtained by the Trophic State Index (IET)\; the index was determined by the high values of the concentration of chlorophyll a, phosphates and the depth of the water mirror indicated by the Secchi disc.